27 Prehospital stroke code. Experience in an argentinean emergency medical service. (26th April 2019) - Apesteguía, A; Savia, A; Farías, A; Muller, A; Kamijo, M; Yaryour, C; Sorkin, E; Allende, M
Abstract : Background: Stroke is a time dependent medical emergency 1 that requires the coordinated action of the pre and in-hospital teams to improve the results. 2 We present the epidemiological characteristics of the population requesting medical attention to a private EMS identified by the telephone operator with activation of a Prehospital Stroke Code (PSC). Method: Observational, retrospective, cross-sectional and descriptive study based on records made through the App Stroke Code v1.0 (internal development) from 01/09/2018 to 31/1/2019. n=97 cases. The data was transferred to a Microsoft Excel spreadsheet and to Epi Info v7.2.2.1 for analysis. Results: PSC was activated in 97 cases. 58 has a suspected Stroke and in 39, the code was canceled by on-scene-EMS team due alternative prehospital diagnosis. The mean age was 78 y/o. 44patients (76%) consulted within three hours of the onset of symptoms. CINCINATTI-prehospital scale average on arrival was 2 points. 100% of patients with CINCITATTI 0–1 consulted after 3 hs (15) (p0.03). On patients with CINCINATTI-score of 3, 97% (p.0038) were hypertensive at the time of the consultation. No hypoglycaemia was found. Of the 58 suspected stroke cases, 16 received some form of reperfusion treatment (rTPA IV, thrombectomy-intraarterial rTPA or combination). The remainder 43 patients who did not receive reperfusion treatment were mainly due to: Alternative in-hospital diagnosis, out of therapeutic window and Intracranial bleeding. The average door to needle time was 37 minutes. Conclusion: Patients more symptomatic consulted earlier 27% of the patients received reperfusion therapy, dramatically surpassing the average of our country (1% according to the RENACER registry3). References: Saver JL. Time Is Brain - Quantified. Stroke 2006;37:263–266. Caputo LM, Jensen J, Whaley M, et al . How a CT-Direct Protocol at an American Comprehensive Stroke Center Led to Door-to-Needle Times Less Than 30 Minutes. The Neurohospitalist 2017, Vol. 7(2) 70–73. Sposato LA, Esnaola MM, Zamora R and the ReNACer Investigators. Quality of ischemic stroke care in emerging countries: the Argentinian National Stroke Registry (ReNACer). Stroke 2008 Nov;39(11):3036–41. Conflict of interest: None. Funding: None.